2014
DOI: 10.1038/ncomms4837
|View full text |Cite
|
Sign up to set email alerts
|

Low abundance of the matrix arm of complex I in mitochondria predicts longevity in mice

Abstract: Mitochondrial function is an important determinant of the ageing process; however, the mitochondrial properties that enable longevity are not well understood. Here we show that optimal assembly of mitochondrial complex I predicts longevity in mice. Using an unbiased high-coverage high-confidence approach, we demonstrate that electron transport chain proteins, especially the matrix arm subunits of complex I, are decreased in young long-living mice, which is associated with improved complex I assembly, higher co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
151
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 70 publications
(91 reference statements)
16
151
1
Order By: Relevance
“…However, neither abundance nor turnover of ND‐1 changed with age in either muscle. The nonuniform effects of age on complex I subunit abundance reported here are consistent with the loss of coordination between nuclear and mitochondrial‐encoded subunits of the respiratory chain recently described in aging muscle (Gomes et al ., 2013; Miwa et al ., 2014), although the change reported here (increased nuclear‐encoded and ND5 subunits) was dissimilar to that reported by Gomes et al . (decreased mitochondrial‐encoded subunits).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…However, neither abundance nor turnover of ND‐1 changed with age in either muscle. The nonuniform effects of age on complex I subunit abundance reported here are consistent with the loss of coordination between nuclear and mitochondrial‐encoded subunits of the respiratory chain recently described in aging muscle (Gomes et al ., 2013; Miwa et al ., 2014), although the change reported here (increased nuclear‐encoded and ND5 subunits) was dissimilar to that reported by Gomes et al . (decreased mitochondrial‐encoded subunits).…”
Section: Discussioncontrasting
confidence: 92%
“…(decreased mitochondrial‐encoded subunits). Increased content of complex I proteins with age, specifically those of the matrix arm, has been linked to decreased lifespan and oxidative stress (Miwa et al ., 2014); thus, a breakdown in stoichiometry in respiratory subunits is expected to lead to poor assembly and function of complex I that would result in the decreased mitochondrial respiratory efficiency and elevated mitochondrial oxidative stress observed here. Our data further implicate complex I as a focal point for regulation of mitochondrial quality and age‐related changes in mitochondrial function.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…3C). This is consistent with recent work showing different states of subcomplex I aggregates in aging (32). Interestingly, we observed that the only complex I subunit that was distributed equally in both cell types was NADH:ubiquinone oxidoreductase core subunit S1 (NDUFS1) (Fig.…”
Section: Modulation Of Complex I Assembly Into Supercomplexes Alters Rossupporting
confidence: 81%
“…24 who showed significant down‐regulation of prohibitin under oxidative stress in the rat testis induced by doxorubicin injection. The present report is the first to show the involvement of PHB in mitochondrial ROS generation of human sperm, consistent with the findings in endothelial 12 and Hela cells 25. The mechanism for the increased generation of mitochondrial ROS might be related to a disruption of mitochondrial electron transport flow in complex I of mitochondrial inner membrane, as reported by Koppers et al .…”
Section: Discussionsupporting
confidence: 93%